(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article analyzes the pedagogical significance of the use of electronic educational resources in primary grades, their impact on the learning process and their role in improving the quality of education. The possibilities of electronic textbooks, multimedia tools, interactive platforms and digital educational resources in developing students’ cognitive activity, independent thinking and learning motivation are highlighted. Methodological recommendations for increasing the effectiveness of the use of electronic educational resources are also developed